Сетевые сообщества-ресурс стратегии развития образовательной организации - Мендибаев, Д.Б. (My University, 2016)
In this article I want to reveal a model of the network of professional interaction in mind the educational organization as a mechanism design and implementation experience of innovative activity of the school and development of professional competence of education workers.
Keywords: professional networking; personal development teacher; innovative activity; educational institutions